O ensino de artes visuais com a utilização do ambiente virtual de aprendizagem Edmodo: um estudo com alunos de uma escola pública de Paço do Lumiar, MA - Pereira, Evaldo Magno Anchieta (2016)
This research concerns the teaching-learning process in Visual Arts, mediated by use of Edmodo, a virtual learning environment available from Internet. We have reported ethnographic study of pedagogical practice took as a reference point an experience of b-learning developed, with use of the digital resource, obtained in a school affiliated to the public network of Maranhão State with 242 highschool students. We have used as data collection instruments: participant observation, logbook, questionnaires and other methods. We have used questionnaires as data collection instruments. We have described: a) the features and pedagogical possibilities provided by that platform as a didactic asset; b) the elements which belong to the required profiled for contemporary educator and, in special, for the art educator dealing with digital native generation; c) the challenges faced by a teacher along his pedagogical practice, concerning the use of Information and Communication Technologies. We have discussed about the use of Web 2.0 tools as didactic assets, emphasizing the advantages and difficulties of virtual space utilization as an alternative to complement on line the process of teaching-learning in Visual Arts implemented in classroom. We have also analyzed the pedagogical possibilities of Edmodo as an alternative resource for teaching-learning in Visual Arts, dialoguing with the Triangular Approach and with theoretical schools of thought as well as with contemporary methodologies for learning process. We realized that VLE's use, along with other available resources in cyberspace, contributes in a substantial way to the improvement of teaching-learning process in Visual Arts.